2010
DOI: 10.1152/jn.00892.2009
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Targets in Smooth or Apparent Motion Along the Vertical in the Human Brain: An fMRI Study

Abstract: Neural substrates for processing constant speed visual motion have been extensively studied. Less is known about the brain activity patterns when the target speed changes continuously, for instance under the influence of gravity. Using functional MRI (fMRI), here we compared brain responses to accelerating/decelerating targets with the responses to constant speed targets. The target could move along the vertical under gravity (1g), under reversed gravity (Ϫ1g), or at constant speed (0g). In the first experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 74 publications
5
41
0
Order By: Relevance
“…This time shift indicates an influence of the orientation relative to visual gravity on response timing that could be attributed to the anticipation of the effects of visual gravity on self-motion along the vertical, but not the horizontal orientation. Finally, precision in TTP estimates was higher during vertical fall than when traveling at constant speed along the vertical orientation, consistent 1 3 network of areas including the posterior-insula and the temporo-parietal junction (Indovina et al 2013, Maffei et al 2010Miller et al 2008;Bosco et al 2008).…”
Section: Introductionsupporting
confidence: 57%
“…This time shift indicates an influence of the orientation relative to visual gravity on response timing that could be attributed to the anticipation of the effects of visual gravity on self-motion along the vertical, but not the horizontal orientation. Finally, precision in TTP estimates was higher during vertical fall than when traveling at constant speed along the vertical orientation, consistent 1 3 network of areas including the posterior-insula and the temporo-parietal junction (Indovina et al 2013, Maffei et al 2010Miller et al 2008;Bosco et al 2008).…”
Section: Introductionsupporting
confidence: 57%
“…The previously mentioned performance advantages for +1g conditions were here accompanied by differential brain activation in insular cortex, temporoparietal junction, premotor and supplementary motor areas, middle cingulate cortex, postcentral gyrus, posterior thalamus, putamen and medial cerebellum (Indovina et al, 2005). This was replicated by Miller et al (2008) to account for different variations such as context; and another study added 0g motion to the comparison and found similar differential activations between 1g and 0g and between 1g and −1g (Maffei et al, 2010). Furthermore, a causal role of the temporo-parietal junction was established through TMS: hyperpolarization of this area lead to a significant performance decrease when catching objects governed by 1g, but not for objects governed by −1g (Bosco et al, 2008).…”
Section: Gravity Information In Vision Related Processing: What Is Itmentioning
confidence: 67%
“…An internal model of gravity during these tasks recruited activation at of PIVC region, which was similarly activated by peripheral vestibular stimulation (McIntyre et al, 2001; Indovina et al, 2005). More recently, Maffei et al (2010) found that visual object motion with a gravitational acceleration profile activated insula cortex and inferior parietal cortex. Both visually seen motion and unseen apparent motion cues similarly activated these regions.…”
Section: Part Two: Vestibular Contributions To Bodily Self-related Comentioning
confidence: 99%